2008
DOI: 10.1108/02686900910919910
|View full text |Cite
|
Sign up to set email alerts
|

Management accounting practices in the Greek hospitality industry

Abstract: Purpose-The purpose of this paper is to report the level of adoption and the benefits derived from traditional and contemporary management accounting practices in the Greek hospitality industry. Design/methodology/approach-An empirical survey via questionnaires was conducted on a sample of 85 leading hotels in Greece. Descriptive statistics on the adoption level, the relative benefits and future emphasis of individual practices provide the basis for discussion. Findings-The adoption rates for many recently dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
1
25

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 42 publications
7
55
1
25
Order By: Relevance
“…Moreover, studies conducted in Arab counties confirm the same conclusion (Rababa'h (2014); McLellan and Moustafa (2013)) Furthermore, Pavlatos and Paggios (2009) concluded that traditional absorption costing and variable costing are the most used cost accounting practices.…”
Section: Financial Measure(s)supporting
confidence: 60%
“…Moreover, studies conducted in Arab counties confirm the same conclusion (Rababa'h (2014); McLellan and Moustafa (2013)) Furthermore, Pavlatos and Paggios (2009) concluded that traditional absorption costing and variable costing are the most used cost accounting practices.…”
Section: Financial Measure(s)supporting
confidence: 60%
“…Α possible reason for this is that larger organizations have relatively greater access to resources to experiment with the introduction of more sophisticated accounting systems. Pavlatos and Paggios (2009b) report similar results in the hospitality industry.…”
Section: Sizesupporting
confidence: 74%
“…Tai interviewed a range of industry personnel in order to identify the reasons for this and found that, although there was considerable knowledge of the theory of ABC, there was a low understanding of how it might be used in hotels (Burgess and Bryant, 2001). Despite the aforementioned results, Pavlatos and Paggios (2009b;2009c) found that Activity Based Costing diffusion in the hospitality industry in Greece is considered very satisfactory. Pavlatos and Paggios (2009c) found that ABC systems in hospitality industry are not excessively detailed, as they include a small number of cost drivers and calculate the cost of a rather small number of activities, such as housekeeping, check in/out, reservation, food production/service, marketing and general administration.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…MA practices were studied outside the Czech Republic in dozens studies such as Chenhall and Langfield-Smith (1998), Wijewardena and Zoysa (1999), Joshi (2001), Hyvönen (2005), AbdelKader and Luther (2006), Pavlatos and Paggios (2009), Angelakis and al. (2010), Yalcin (2012), or Pavlatos and Kostakis (2015).…”
Section: Theoretical Frameworkmentioning
confidence: 99%